PS02.108: EFFECTS OF PREOPERATIVE CHEMOTHERAPY FOR ADVANCED ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (14th September 2018) - Kamio, Yukinori; Hachiya, Osamu; Fujimoto, Hiroto; Takasu, Naoki; Toda, Makoto; Suzuki, Takefumi; Sato, Tamie; Nakano, Ryo; Nozu, Shintaro; Kimura, Wataru
Abstract: Background: In Japan, preoperative chemotherapy followed by surgery is the standard treatment for clinical stage II or III, excluding T4 thoracic esophageal squamous cell carcinoma (SCC). Here, we investigated the efficacy of preoperative chemotherapy in our hospital. Methods: From January 2010 through December 2017, 33 patients with clinical stage II/III esophageal SCC underwent esophagectomy after preoperative chemotherapy with two cycles of cisplatin and 5-fluorouracil. Overall survival (OS) and clinical and pathological tumor responses were retrospectively evaluated. In addition, fluorodeoxyglucose (FDG) uptake was assessed by FDG-positron emission tomography/computed tomography (PET/CT). Results: There were 9 patients with stage II and 24 with stage III esophageal SCC, and two cycles of chemotherapy were completed by 27 patients (81.8%). Three-year OS rates were 100% in patients with stage II and 66.7% in patients with stage III esophageal SCC, whose observation period exceeded beyond 3 years. Of the 33 patients who showed a clinical response at the primary site, 22 (66.7%) had a partial response (PR), and a 3-year OS of 85.7%, while 4 (12.1%) had a complete response (CR), and a 3-year OS of 100%. In regards to pathological response, as evaluated using The Japan Esophageal Society histological evaluation criteria, 3 patients (9.1%) were classified as grade 0, 18 (54.5%) as grade 1a, 4 (12.1%) as grade 1b, 6 (18.2%) as grade 2, and 2 (6.1%) as grade 3. Of the 22 patients who achieved PR, 14 (63.6%) were classified as either grade 0 or 1a. On the other hand, when we compared the maximum standardized uptake value (SUVmax) of FDG − PET/CT at the primary site before and after preoperative chemotherapy, the patients with high decreasing rates mostly belonged to the grade 1b-3 group. The OS rate tended to be higher in the grade 1b-3 group than in the grade 0–1a group. Conclusion: Our present results suggest that, although pathological responses do not necessarily correspond to clinical tumor reduction, a good pathological response is potentially related to a better prognosis. Furthermore, the FDG uptake value may reflect pathological effects that occur owing to preoperative chemotherapy. Disclosure: All authors have declared no conflicts of interest.